Raman spectroscopic insights into the glass transition of poly(methyl methacrylate). Issue 2 (7th January 2021) - Bertoldo Menezes, D.; Reyer, A.; Benisek, A.; Dachs, E.; Pruner, C.; Musso, M.
Abstract : Poly(methyl methacrylate) (PMMA) is a very versatile polymer which is used as a glass substitute or as an economical alternative to polycarbonate for many types of important applications, due to its particular physical properties. Abstract : Poly(methyl methacrylate) (PMMA) is a very versatile polymer which is used as a glass substitute or as an economical alternative to polycarbonate for many types of important applications, due to its particular physical properties. In this study we deal with the Raman spectroscopic characterization of the glass transition of PMMA, the value of the glass transition temperature being generally a decisive parameter for determining the application of polymers. The information obtained by two-dimensional correlation spectroscopy (2DCOS) analysis and perturbation–correlation moving-windows spectroscopy (PCMW2D) analysis of the temperature dependent depolarized Raman spectra enabled us to recognize that the glass transition of PMMA is ruled by intermolecular interactions which influence the vibrational modes of the molecular groups associated with ν (CO), δ a (C–H) of α-CH3 and/or O–CH3, ν (C–O–C), ν (C–COO), and ν (C–C–O). This information was employed for the temperature dependent study of the Raman shift and of the full width at half maximum of the Raman peaks obtained through anisotropic and isotropic Raman spectra, of the depolarization ratio, of the Raman spectroscopic noncoincidence effect, and of the Raman peak intensities represented by Arrhenius-type plots, all results supporting the outcomes of this work. The comparison with results obtained by differential scanning calorimetry and with published results in molecular dynamics studies was also part of this work. As the main result, one can highlight the peak associated with the ν (C–O–C) stretching mode at around 812 cm −1 as the one which presents the better outcome for explaining the glass transition from the molecular point of view.